Sensitive species survey, Peterson Air Force Base, 2017-2018 - Sovell, John, author; Doyle, Georgia, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2018)
The plant survey identified 165 species, of which 124 were native species. Six B‐List Colorado noxious weed species were found in 2017‐2018. The rare plant species targeted in the survey included two federally threatened species, Ute ladies' tresses orchid (Spiranthes diluvialis) and Colorado butterfly plant (Oenothera coloradensis). Both of these species have low likelihood of occurring at Peterson AFB as they are wetland dependent and generally occur in undisturbed habitat. The tallgrass prairie community in Peterson East originally documented in 1997 continues to be in good condition though decreasing in size with continued development of infrastructure on the base.
Prepared for: U.S. Department of Defense, Peterson Air Force Base.
December 2018.
Keywords: plant survey; native species; noxious weed species; rare plant species; rare animals; Peterson Air Force Base